Analysis of ankle injuries in badminton players at Chinese universities - Yang, Z.; Wang, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: This study aimed to investigate the rate of ankle injuries in badminton players at Chinese universities. Major factors causing the injuries were analyzed in this study and it was anticipated that the findings of the study might be useful in reducing the rate of ankle injuries in badminton players. Methods A comprehensive review of the relevant literature was undertaken involving 80 relevant studies from 1979 to 2007, including 30 with closely-related findings. A survey of injuries was conducted and data was obtained and analysed for 328 badminton players from 35 Chinese universities. Observational data was also obtained on the badminton players during the Chinese University Badminton Tournaments from 2004-2007 together with interviews of badminton players, coaches, and sport medicine doctors to gainm insight into the possible causes of injury. Survey data was analysed using the SPSS 13.0. Results The results of the injury survey across the sample population the rate of ankle injuries ranked the highest (49.5%), and there was no significant difference (p>.05) between males and females. Traumatic ankle joint injuries accounted for 25.2%, lateral ligament injuries, 16.8%, peritendonitis of the Achilles tendon accounted for 5.0%, medial ligament 4.1%, osteoarthropathy of the ankle 3.4%, torn ligaments at the Achilles` tendon accounted for 2.3%, and ankle fractures accounted for 2.1%. The major cause of these ankle injuries was a slippery ground surface, followed by weak leg strength, lack of warm-up and improper movements. A majority of the injuries took place during jumping. Discussion Ankle injuries ranked the highest of all injuries among the badminton players and were significantly related to their health and performance. The rate of their ankle injuries has surpassed that of professional badminton players (11.4%) and recreational badminton players (5.3%). As University badminton players lack the professional instruction and systematic training, coaches and players should enhance their awareness of strategies to reduce the risk of ankle injuries. In addition, it is suggested that organisers of university badminton teams should improve their training environments, especially training facilities and equipment.